Temporal biomarker concentration patterns during the early course of acute coronary syndrome - Eggers, Kai; Batra, Gorav; Lindahl, Bertil; Lakic, Tatevik Ghukasyan; Lindbäck, Johan; Budaj, Andrzej; Cornel, Jan H.; Giannitsis, Evangelos; Katus, Hugo; Storey, Robert F.; Becker, Richard C.; Siegbahn, Agneta; et al. (Clinical chemistry and laboratory medicine, 2024)
Objectives: Biomarker concentrations and their changes during acute coronary syndrome (ACS) provide clinically useful information on pathophysiological processes, e.g. myocardial necrosis, hemodynamic stress and inflammation. However, current evidence on temporal biomarker patterns early during ACS is limited, and studies investigating multiple biomarkers are lacking. Methods: We measured concentrations of high-sensitivity cardiac troponin T (hs-cTnT) and I (hs-cTnI), NT-terminal pro-B-type natriuretic peptide, C-reactive protein, and growth-differentiation factor-15 (GDF-15) in plasma samples obtained at randomization in ACS patients from the PLATelet inhibition and patient Outcomes (PLATO) trial. Linear regressions with interaction analyses were used to investigate the associations of biomarker concentrations with the time from symptom onset and to model temporal biomarker concentration patterns. Results: The study population consisted of 16,944 patients (median age 62 years; 71.3% males) with 6,853 (40.3%) having ST-elevation myocardial infarction (STEMI) and 10,141 (59.7%) having non-ST-elevation ACS (NSTE-ACS). Concentrations of all biomarkers were associated with time from symptom onset (pinteraction <0.001), apart for GDF-15 (pinteraction =0.092). Concentration increases were more pronounced in STEMI compared to NSTE-ACS. Temporal biomarker patterns for hs-cTnT and hs-cTnI were different depending on sex whereas biomarker patterns for the other biomarkers were similar in cohorts defined by age and sex. Conclusions: Temporal concentration patterns differ for various biomarkers early during ACS, reflecting the variability in the activation and duration of different pathophysiological processes, and the amount of injured myocardium. Our data emphasize that the time elapsed from symptom onset should be considered for the interpretation of biomarker results in ACS.